Pengaruh Citra Koperasi Syariah Terhadap Partisipasi Anggota Koperasi Syariah BMT Itqan - Arman Maulana (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2020)
The problem with the Bmt Itqan Sharia Cooperative has not reached the target of gathering members, even though its age is more than one year. New members reached as much as 75%. Because cooperatives are a collection of people or business entities that have the same goal. Then this unachieved goal is a problem. This might be because the image of cooperatives is not in accordance with the expectations of the community so that people are not interested in becoming members of cooperatives. This research method is descriptive and verification. With Spearman Rank data analysis, Simple Linear Regression and Coefficient of determination and t test. With a sample of 40 members. Based on the calculation above, it is known that: Loyalty of members is influenced by the image of the cooperative by 84.4%, while the remaining 15.6% is influenced by other factors outside the image of the cooperative. Thus the image of cooperatives in the eyes of cooperative members has a significant influence on the loyalty of cooperative members. For t arithmetic can be calculated with SPSS resulting in a value of 4,020. The t-count value is then compared to the table value above, as follows: T-count (4,020)> T-table (1,684). From these results it can be stated that the null hypothesis is rejected, which means that there is a significant influence of the image of the cooperative on member loyalty.